A Sense of Fellowship: Mindfulness Improves Experienced Interpersonal Benefits and Prosociality in A Military Aviation Unit. Issue 2 (3rd April 2021) - Meland, Anders; Hoebeke, Elena; Pensgaard, Anne Marte; Fonne, Vivianne; Wagstaff, Anthony; Gaden Jensen, Christian
ABSTRACT: Objective : Explore how personnel in a military aviation unit experienced personal as well as interpersonal aspects concerning their participation in a group-based four-month MBT programme. Background : mindfulness-based training (MBT) have been used as a personal stress management tool in stressful working environments, including military aviation. There is little knowledge about the interpersonal mechanisms involved when engaging in MBT. Method : Adhering to Grounded Theory (GT), we conducted post-intervention interviews with 42 programme participants. We selected 30 interviews with evidence of interpersonal effects for in-depth analyses to build a theoretical model of the pathways through which interpersonal effects might develop. Results : The majority of the interviewees (30/42 = 71%) experienced significant interpersonal effects from MBT. The in-depth analyses revealed an increase in the common theme "Sense of Fellowship" (SOF). SOF comprised three primary change processes: "Attention to others, " "Self-observation" and "Reflection." In addition, five behavioral changes emerged: "Direct communication, " "Increased patience, " "Decreased anger expression, " "Calmness, " and "Acceptance." Finally, four contextual factors appeared to have particular importance for the development of SOF: "Plenary sessions, " "Sharing experiences, " "Doing something new together, " and "Sitting in silence." Conclusion : These findings indicate that MBT has prosocial effects in a military aviation setting, and the constructed model contributes theoretically by suggesting how these psychosocial effects may arise and develop.